Teologi, Studi Biblika, dan Misi - Ailsa Barker (Asosiasi Teolog Indonesia, 2017)
Missional hermeneutics is the interpretation of Scripture as it relates to the missionary task of the church. Four elements comprise a missional hermeneutics: 1) the missional trajectory of the biblical story being the foremost element, which also underlies the other three, 2) a narrative throughout Scripture centered on Christ and intended to equip the people of God for their missional task, 3) the missional context of the reader, in which attention moves from the task of equipping to the community being equipped, a community that is active, and 4) a missional engagement with culture and the implications thereof. Through the life of God’s people an alternative is offered, together with an invitation to come and join. Because the separation of theology from the mission of the church has distorted theology, all theology needs to be reformulated from the perspective of missio Dei and from the realization that the church is a sent community, missional in its very being. A missional hermeneutics bears implications upon the congregation, worship, preaching, discipleship, education, ministerial training, and the missionary task in multicultural contexts.